Analisis Studi Kelayakan Bisnis Pembenihan Ikan Lele Sangkuriang (Studi Kasus: Upr Jiponk Farm) - Eka, Dwi Laksmita (BISMA : Business and Management Journal, 2023)
The fish farming process requires good care and management. In its implementation, it requires costs in managing it by procuring production factors. Every out-of-pocket expense or income earned by a business actor will affect the financial flow, profits and sustainability of the business. The aim of this research is to determine the feasibility of developing a catfish seed cultivation business from the marketing aspect related to consumer interest, business partners and determining the price of catfish seeds. The methods used in this research are quantitative and qualitative methods in the form of survey and interview methods. The research results show that UPR Jiponk Farm has 2 seeding business partners, namely, UPR Sopi Farm and UPR Zaki Farm. The production costs of the catfish hatchery business run by UPR Jiponk Farm are IDR 10,100,000. The average sales of UPR Jiponk Farm catfish seeds per month in 2019 with a size of 3-4 cm was 62,834 seeds with a selling price of IDR 150/fish. So the average revenue from the UPR Jiponk Farm catfish hatchery business is IDR 9,425,100. Meanwhile, the profit from a catfish hatchery business for one year averages IDR 7,825,100.